Initial results from the hotspot detection scheme for protection of plasma facing components in Wendelstein 7-X. (May 2019) - Ali, A.; Niemann, H.; Jakubowski, M.; Pedersen, T. Sunn; Neu, R.; Corre, Y.; Drewelow, P.; Sitjes, A. Puig; Wurden, G.; Pisano, F.; Cannas, B.; Gao, Y.; et al.
Highlights: We present automatic, near real-time detection of hot spots and identification of surface layers on W7-X test divertor. Events such as surface layers due to erosion and deposition of carbon tiles lead to overestimation of surface temperature. We have developed and successfully tested a method to classify surface layers and benchmark the performance of the method with the Tore Supra IR data operating with actively cooled carbon PFCs. For the surface layers analysis at W7-X, the results were compared with a best fit estimate of the heat transmission coefficient (ś) which is used to calculate heat flux onto the divertor in the presence of surface layers The numerical method shows promising results of detecting surface layers on inertially as well as water-cooled plasma-facing components. Abstract: One of the main aims of Wendelstein 7-X (W7-X), an advanced stellarator, is to investigate the quasi-steady state operation of magnetic confinement devices for nuclear fusion, for which power exhaust is an important issue. A dominant fraction of the energy leaving from the confined plasma region will be removed by 10 so-called island divertor units, which are designed to sustain a maximum heat flux of up to 10 MW m − 2 . An essential prerequisite for the safe operation of a steady-state device is automatic detection of hot spots and other abnormal events. Simple temperature limits in infrared (IR) thermographic images will not be enough on their own, because of plasma-generated surface coatings and other effects summarized in the following. To protect divertor elements from overheating, and to monitor power deposition onto the divertor elements, near real-time hotspot detection algorithms for the analysis of carbon plasma facing components (PFCs) were implemented and tested in the GLADIS facility. One of the difficulties in hotspot detection in a carbon-based machine is the deposition of plasma impurities as layers with a reduced thermal connection to the underlying bulk material. We have developed and successfully tested a method to classify surface layers and benchmarked the performance of the method with the Tore Supra IR data operating with actively cooled carbon PFCs. The surface layers can be detected in a steady plasma discharge during the initial rise and decay in temperature when a strike line touches parts of the divertor or wall. It can also be detected by modulating electron cyclotron resonance heating (ECRH) input power. This feature allows detection of overheated areas while reducing false positives. For the recent operational campaign, inertially cooled test divertor units (TDU) were installed to prepare for steady-state operation with water-cooled divertor units. Automatic, near real-time detection of hot spots and identification of surface layers in the W7-X divertor are presented. Results are compared with a best fit estimate of the heat transmission coefficient α which is used to calculate heat flux onto the divertor in the presence of surface layers.